Origin of giant dielectric response in LiCuNb3O9 distorted perovskite ceramics. Issue 4 (April 2017) - Chen, Xiuli; Ma, Dandan; He, Fen; Huang, Guisheng; Zhou, Huanfu
Abstract: LiCuNb3 O9 ceramics with the distorted cubic perovskite structure were prepared by a solid-state reaction method. The ceramic exhibited a very large value of permittivity (∼4.4 × 10 4 at 100 kHz) at room temperature (∼300 K) and a low-temperature dielectric relaxation behaviour following the Arrhenius law. The origin of the giant dielectric response of the LiCuNb3 O9 ceramics was correlated with the structure of the ceramics. The barrier layers in the grain boundaries and the mixed-valent structure of Cu + /Cu 2+ were found to contribute to the giant permittivity of the ceramics and confirmed by X-ray spectroscopy and complex impedance spectroscopy analyses.